2015
DOI: 10.1007/s10973-015-5196-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polyoxymethylene molar mass on the oxidative thermal degradation of its nanocomposites with hydroxyapatite

Abstract: In this paper, the influence of mass-average molar mass (M w ) of polyoxymethylene (POM) copolymer on the thermooxidative degradation behavior of its nanocomposites with hydroxyapatite (HAp) is reported. POM copolymers' thermal stability slightly decreases with a decrease in mass-average molar mass. Thermal stability of POM/HAp nanocomposites is lower in comparison with pure POM, and it gets lower with a decrease in massaverage molar mass of POM copolymer. For POM copolymer with the highest molar mass, thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Approximately 10 mg of the sample was used for each experimental run for each of the samples. The role of mass transfer phenomena was also experimentally verified by comparing the TG/DTA plots for the same material, but at: (1) different particle sizes (0.075, 0.151, and 0.211 mm) (for internal diffusion) and (2) different flow rates (40,50, and 60 mL min -1 ) (for external diffusion).…”
Section: Thermogravimetric Analysis (Tg/dta) Combustion Kineticsmentioning
confidence: 94%
See 1 more Smart Citation
“…Approximately 10 mg of the sample was used for each experimental run for each of the samples. The role of mass transfer phenomena was also experimentally verified by comparing the TG/DTA plots for the same material, but at: (1) different particle sizes (0.075, 0.151, and 0.211 mm) (for internal diffusion) and (2) different flow rates (40,50, and 60 mL min -1 ) (for external diffusion).…”
Section: Thermogravimetric Analysis (Tg/dta) Combustion Kineticsmentioning
confidence: 94%
“…The Netzsch Thermokinetics 3.1 (version 072010) was used for processing of the non-isothermal data [3,39,40]. The activation energies (E), which depend on the degree of conversion (a), were evaluated by this software package which allows the evaluation of the dependence of E on a by means of FR and FWO model-free methods.…”
Section: Processing Of the Experimental Datamentioning
confidence: 99%
“…The course of the curves shown in Figures 6-8 confirmed that the decomposition of homopolyacetals can be a single or multi-stage process depending on their origin and thermal history, which may result, among other factors, from only univariate or invariant apparent activation energy as the reaction progresses. Following the literature data, it would be expected that the activation energy for the homopolymer should be in the range of 40-160 kJ/mol [3,4]. In the case of the graph of changes in apparent activation energy as a function of the partial mass loss of the POM-P sample, a similar trend of changes in activation energy was observed in the range of 0.4-0.8 weight loss (regardless of the nature of the atmosphere in which TG measurements were carried out and the calculation model used).…”
Section: Kinetic Modelling Of Thermo-oxidative Degradation Processmentioning
confidence: 99%
“…Polyoxymethylene (polyacetal, polyformaldehyde, and POM), is a popular thermoplastic engineering polymer due to its good mechanical properties. It has a wide range of applications mainly in the mechanical industry [ 1 , 2 , 3 ]. However, POM is thermally unstable because its repeating oxymethylene chain units are usually terminated with hemi formal terminals [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between various polymers and the solid particles using the thermogravimetric methods are subject of numerous research [38][39][40][41][42][43][44][45][46][47][48][49][50]. Figures 7-10 present the TG, DTA and DTG curves for the chromium (III) oxide samples, both unmodified and modified with the adsorption layer formed by the analyzed homo-and copolymers.…”
Section: Thermogravimetric Analysis Of the Poly(l-aspartic Acid) Homomentioning
confidence: 99%